43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-1420
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Sensing and Mitigation of Lean Blow Out in Premixed Flames

Abstract: This paper describes a method for detecting and preventing lean blow out (LBO) in a premixed, swirl stabilized combustor. The acoustic signal is filtered to detect localized extinction 'events', which increase in frequency as the flame equivalence ratio, φ φ φ φ, approaches the LBO limit, φ φ φ φ LBO. As the flame becomes leaner, φ φ φ φ LBO can be effectively shifted to lower equivalence ratios by redirecting a fraction of the total fuel into a central, premixed pilot. This actuation can increase the equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Several methods have been used to achieve stabilization in combustion systems, such as pilot flames, oxygen-rich coflows, bluff bodies, and swirling flows. Pilot flames are routinely used to stabilize laboratory scale, nonpremixed [1], [2], and premixed [3]- [5] flames. A pure oxygen coflow surrounding a jet flame was demonstrated to be successful in stabilizing laboratoryscale diffusion flames [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to achieve stabilization in combustion systems, such as pilot flames, oxygen-rich coflows, bluff bodies, and swirling flows. Pilot flames are routinely used to stabilize laboratory scale, nonpremixed [1], [2], and premixed [3]- [5] flames. A pure oxygen coflow surrounding a jet flame was demonstrated to be successful in stabilizing laboratoryscale diffusion flames [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies revealed that unlike the present method, other methods in literature like those proposed by Gutmark and coworkers [13] and Lieuwen, Seitzman and coworkers [14][15][16] perform very well for L fuel = 35 cm but their performance deteriorates as the fuel inlet is moved closer towards the dump plane. These results have been presented in our earlier publications [23].…”
Section: Lbo Detectionmentioning
confidence: 61%
“…Refs. [14,15]) signals close to LBO. A comparison between the two in the same experimental setup [16] portrays optical methods as the superior choice on account of faster response time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot flames have been implemented in laboratory scale, nonpremixed flames [1][2] and premixed flames. [3][4][5] A pure oxygen coflow surrounding a jet flame was demonstrated in laboratory-scale diffusion flames. 6 Bluff bodies or swirl stabilization mechanisms have been used in premixed and partially premixed flames to generate a recirculation zone which preheats the reactants, resulting in increased flame stability.…”
Section: Introductionmentioning
confidence: 99%